Comparative Urban Politics : Power and the City in the U.S , Canada, Britain and France - KEATING, Michael ([Tidak Terdaftar], 1991)
Based on the experience of the United States, Britain and France, this book traces the opening of urban political structures to new influences as a result of political organization, social change and the growth of neighbourhood organizations. It compares forces tending to reduce city autonomy, including the concentration and mobility of capital, the growth of the national welfare state, the nationalization of party politics and fiscal competition between national and local governments. In conclusion, Professor Keating examines the potential conflict between the politics of growth and the politics of redistribution and assesses the prospects for effective democratic and local politics.